Attitudes and Perceptions Towards Nursing Profession Among Nursing Students at Hue University of Medicine and Pharmacy - Ba Hai Mai; Thi My Yen Ho; Thi Thu Thao Nguyen; Le Thi Thanh Phan; Thi Huong Hoang; Nguyen Thi Anh Phuong (Journal of Problem-Based Learning, 2018)
Objectives To describe the attitudes and perceptions toward nursing profession among nursing students at Hue University of Medicine and Pharmacy (Hue UMP). Method The mixed method study involved 319 nursing students from first to fourth-year. Quantitative data was collected by using the Attitudinal Scale for Nursing Profession, and participants’ subjective perception of nursing profession was collected by asking participants questions such as: "How do you feel about nursing and nursing profession?" Results The quantitative results showed that the mean score of nursing students’ attitudes toward nursing profession was 148.76 (SD = + 37.29). The average score on satisfaction for nursing profession varies from 40 to 200. The qualitative findings show perceptions classified under 2 emergent themes: 1) A career that requires passion and professionalism 2) High-pressure and a boring career. Conclusion These findings provide a preliminary understanding of nursing students’ attitudes and perceptions toward the nursing profession. The study has implications for both the nursing professors and university: Curricula have to emphasize ways of enhancing student’s positive awareness of the contemporary roles and values of the profession to students. Collaborative studies with other Universities and Colleges will assist in developing stimulus material and learning strategies that will enhance the value of the role of nurses in contemporary Vietnamese health care.